Pengaruh Digital Marketing Dan Brand Image Aplikasi Shopee Terhadap Consumer Trust Karyawan PT Bank Central Asia Tbk Cabang Indrapura Surabaya - Nadia Tamara Effendi; Is Fadhillah; Handy Aribowo (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
Technology progress offers an positive impact for marketing technique become digital marketing as company motivator to improve company performance which has a positive effect for the consumer by make it easier whether make an improvement evaluation for the company. The better assessment that the company get for the digital marketing technique that the company have also enhancement for the better brand image that the company have. With the improvement obtained the brand image of the company also it will increase the quality of service, and the popularity of the products that are owned also a higher level of consumer trust appears as well. The purpose of this study is to find out digital marketing and brand image have a significant influence on consumer trust . The type of research that used in this study is quantitative research with purposive sampling with 61 respondent. The results of this study showed that digital marketing has a significant effect on consumer trust and brand image also has a significant impact on consumer trust.